Dietary Honeysuckle (Lonicera japonica) Extract Enhances Resistance to Infectious Myonecrosis Virus in Whiteleg Shrimp (Litopenaeus vannamei) - Subaidah, Siti; Sumarwan, Joko; Marzuqi, Muhammad; Tridjoko, Tridjoko; Slamet, Bejo; Budi, Darmawan Setia; Pardede, Maria Agustina; Ulkhaq, Mohammad Faizal; Imlani, Ainulyakin; Loh, Jiun-Yan (Jurnal Medik Veteriner, 2025)
This study aimed to investigate the immune response of whiteleg shrimp (Litopenaeus vannamei) to prevent infectious myonecrosis virus (IMNV) infection by incorporating Lonicera japonica water extract into artificial feed. A total of 180 whiteleg shrimp were used in four treatment groups (triplicate) receiving different doses of L. japonica extract in their feed, including treatment A (1% w/w), B (2% w/w), C (3% w/w), and D (without supplementation/control). The dietary treatments were applied twice daily for two weeks. On the 15th day, the shrimp were injected intramuscularly at the fifth abdominal segment with IMNV isolates (100 µL/shrimp) and observed for seven days post-infection (dpi). The parameters observed included hemolymph profile, survival rate, gross clinical signs, and water quality. IMNV infection was confirmed through both external clinical signs and PCR tests. The results showed that the addition of L. japonica water extract to the feed improved the survival rate and immune responses of whiteleg shrimp following the IMNV challenge test. In conclusion, dietary supplementation of L. japonica water extract at a concentration of 2% w/w in artificial feed could serve as a preventive agent against IMNV infection in whiteleg shrimp.